Capabilities-Based Planning for Energy Security at Department of Defense Installations - Samaras, Constantine (RAND Corporation, 2013)
Department of Defense (DoD) installations rely on the commercial electricity grid for 99 percent of their electricity needs, but the U.S. electricity grid is vulnerable to disruption from natural hazards and actor-induced outages, such as physical or cyber attacks. Using portfolio analysis methods for assessing capability options, this paper presents a framework to evaluate choices among energy security strategies for DoD installations.